PENDAMPINGAN PUBLIKASI ILMIAH GURU SMA N 1 MOJOTENGAH, WONOSOBO, JAWA TENGAH - Ahmad Khoiri; Marwiati Marwiati; Achmad Affandi; Kurniawati Mutmainah; Nurma Khusna Khanifa (LPPM Universitas Bina Bangsa, 2022)
Scientific publications for teachers are very important to contribute in solving student problems in school. PKMTN goal is to increase the motivation and culture of writing teacher scientific publications at SMA N 1 Mojotengah Wonosobo. The method of service carried out with the principle of